Pengaruh Lingkungan Keluarga Terhadap Perkembangan Pendidikan Anak Pada Jenjang SMP - Sharla Syafrina Nufriandini; I Ketut Mahardika; Lailiatul Qomariah; Viki Hanimatussyaadah; Rizka Elan Fadila; Firdha Yusmar (Peneliti.net, 2022)
This journal reviews the role of the family in the development of children's character education. Where the family plays an important role in the development of children. Family is the first place for children's education. Children will learn first through the family. This study aims to explain and analyze how the role of the family itself on the development of the child. This type of research is descriptive research and literature review. Descriptive research is a research method that shows the characteristics or phenomena being studied. Until finally this research method mainly focused on explaining the object of research and answering what events or phenomena occurred.